The marketer's handbook : reassessing marketing techniques for modern business - Young, Laurie. 1955- (Chichester, West Sussex, U.K : Wiley, 2011)
"This book has the potential to be a bible for the modern marketer, a reference book that will sit on any marketer's desk or shelf"--
Includes bibliographical references and index.
Keywords: Marketing; BUSINESS & ECONOMICS / Sales & Selling